2003
DOI: 10.1037/0893-164x.17.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pathological Gambling: A Critical Review of the Literature.

Abstract: The legalization and availability of new forms of gambling are increasing in most Western countries. This trend has contributed to the fact that more individuals are developing gambling problems. As a result, there is a need for effective treatments. Although gambling treatment dates several decades, few empirically supported treatments for pathological gambling have been developed. This critical review includes only controlled treatment studies. The primary inclusion criterion was randomization of participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
134
0
24

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(162 citation statements)
references
References 33 publications
4
134
0
24
Order By: Relevance
“…From a theoretical perspective, CBT appears to be the most successful mode of treatment for addictions (Babor et al, 2003;Finney & Moos, 1998;Petry et al, 2006;Toneatto & Ladouceur, 2003) and these approaches appearing to be transferred with success to Internet-based therapy programs (Barak et al, 2008). In Internet therapy, clinician input is markedly reduced compared to face-to-face treatment, with feedback delivered, and decision-trees determined, by the computer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a theoretical perspective, CBT appears to be the most successful mode of treatment for addictions (Babor et al, 2003;Finney & Moos, 1998;Petry et al, 2006;Toneatto & Ladouceur, 2003) and these approaches appearing to be transferred with success to Internet-based therapy programs (Barak et al, 2008). In Internet therapy, clinician input is markedly reduced compared to face-to-face treatment, with feedback delivered, and decision-trees determined, by the computer.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is a need to improve the methodological inadequacy of studies undertaken, by selecting rigorous study designs and dealing carefully with issues pertaining to recruitment of appropriate and sufficiently large samples, randomization, and participant retention. Methodological flaws in treatment studies limit the firm scientific knowledge that can be concluded about the treatment (Toneatto & Ladouceur, 2003). Other important design components to consider include the use of direct behavioral measures as opposed to non-validated self-report ratings to evaluate outcomes; collecting baseline data to assess the actual treatment impact and additional treatment seeking behavior in addition to use of Internet therapy to control for outside therapeutic assistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research into treatments for problem gambling suffers methodological flaws, limiting the extent to which firm conclusions can be drawn about the efficacy of gambling treatments (Blaszczynski, 2005;Dowling, Jackson, & Thomas, 2008;Toneatto & Ladouceur, 2003). Some of these methodological issues include: small sample sizes; a tendency to use measures assessing gambling behaviour in insufficient detail to allow the full range of outcomes to be considered (rather, a preference for use of dichotomous categories such as success or failure can be found); an absence of baseline data; a lack of standardised treatments; little evidence to suggest that treatments were administered reliably; and insufficient attention paid to the mediation or process of behaviour change.…”
Section: Treatment For Problem Gamblingmentioning
confidence: 99%
“…There is sufficient evidence within the published research to suggest that the behavioural treatment approach is likely to have a positive impact, particularly with EGM users, with 30 to 80% of participants abstaining from gambling post-treatment (Echeburúa & Fernández-Montalvo, 2005). However, CBT is credited with holding the greatest amount of empirical support in the treatment of problem gambling (Toneatto & Ladouceur, 2003).…”
Section: Treatment For Problem Gamblingmentioning
confidence: 99%